2022
DOI: 10.3390/biomedicines10112958
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Adiponectin in Breast Cancer

Abstract: Obesity and breast cancer are two major health issues that could be categorized as sincere threats to human health. In the last few decades, the relationship between obesity and cancer has been well established and extensively investigated. There is strong evidence that overweight and obesity increase the risk of postmenopausal breast cancer, and adipokines are the central players in this relationship. Produced and secreted predominantly by white adipose tissue, adiponectin is a bioactive molecule that exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 146 publications
0
10
0
Order By: Relevance
“…Our findings showed that Rooibos extract significantly reduced leptin expression in mature adipocytes, once again reflecting its anti-inflammatory properties. Additionally, there is huge interest in adiponectin and its analogs as a potential therapy, not only for all metabolic syndromes but also for several cancer types [ 43 ]. To our knowledge, our team is the first to reveal that Rooibos significantly increases adiponectin expression in 2D and 3D human primary adipocyte cultures, contrary to the published results on 3T3-L1 murine adipocytes, where adiponectin secretion remained unchanged after Rooibos treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that Rooibos extract significantly reduced leptin expression in mature adipocytes, once again reflecting its anti-inflammatory properties. Additionally, there is huge interest in adiponectin and its analogs as a potential therapy, not only for all metabolic syndromes but also for several cancer types [ 43 ]. To our knowledge, our team is the first to reveal that Rooibos significantly increases adiponectin expression in 2D and 3D human primary adipocyte cultures, contrary to the published results on 3T3-L1 murine adipocytes, where adiponectin secretion remained unchanged after Rooibos treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin which ADIPOQ encodes, is secreted by adipocytes and has various biological effects. Several studies suggest that adiponectin has a protective effect against breast cancer [49]. Adiponectin has been shown to induce autophagic cell death in breast cancer through the activation of the AMPK-ULK1 axis regulated by STK11/LKB1 and trigger breast cancer cell death through fatty acid metabolic reprogramming [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…This concept is now re-emerging (discussed in [146]), due to the implementation of drug repurposing (Denosumab, Metformin, Letrozole, see Suppl. Table ) as well as principally new approaches like adiponectin receptor targeting molecules [147].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%